Pleural Mesothelial Cells Modulate the Inflammatory/Profibrotic Response During SARS-CoV-2 Infection - Matusali, Giulia; Trionfetti, Flavia; Bordoni, Veronica; Nardacci, Roberta; Falasca, Laura; Colombo, Daniele; Terri, Michela; Montaldo, Claudia; Castilletti, Concetta; Mariotti, Davide; Del Nonno, Franca; Capobianchi, Maria Rosaria; et al. (Frontiers in Molecular Biosciences, 2021)
Although lung fibrosis has a major impact in COVID-19 disease, its pathogenesis is incompletely understood. In particular, no direct evidence of pleura implication in COVID-19-related fibrotic damage has been reported so far. In this study, the expression of epithelial cytokeratins and WT1, specific markers of mesothelial cells (MCs), was analysed in COVID-19 and unrelated pleura autoptic samples. SARS-CoV-2 replication was analysed by RT-PCR and confocal microscopy in MeT5A, a pleura MC line. SARS-CoV-2 receptors were analysed by RT-PCR. Inflammatory cytokines from the supernatants of SARS-CoV-2-infected MeT5A cells were analysed by Luminex and ELLA assays. Immunohistochemistry of COVID-19 pleura patients highlighted disruption of pleura monolayer and fibrosis of the sub-mesothelial stroma, with the presence of MCs with fibroblastoid morphology in the sub-mesothelial stroma, but no evidence of direct infection in vivo. In vitro analysis shown that MeT5A cells expressed ACE2, TMPRSS2, ADAM17 and NRP1, plasma membrane receptors implicated in SARS-CoV-2 cell entry and infectivity. Moreover, MeT5A cells sustained SARS-CoV-2 replication and productive infection. Infected MeT5A cells produced interferons, inflammatory cytokines and metalloproteases. Overall, our data highlight the potential role of pleura MCs as promoters of the fibrotic reaction and regulators of the immune response upon SARS-CoV-2 infection.